Synergistic anticancer effects via co-delivery of TNF-related apoptosis-inducing ligand (TRAIL) and doxorubicin using micellar polymer nanoparticles - Lee, A.; Dhillon, S.; Wang, Y.; Pervaiz, Shazib; Yang, Y. (American Chemical Society, 2012)
The use of small molecule drugs in cancer chemotherapy has mostly been limited by dose-dependent toxicity and development of drug resistance resulting from repeated administrations. To overcome such problems, efforts have been made to develop drug delivery systems that can bear multiple therapeutic agents in one system. The purpose of this study is to deliver human tumor necrosis factor (TNF) -related apoptosis-inducing ligand (Apo2L/TRAIL) and doxorubicin (Dox, an anti-cancer drug) with micellar nanoparticles self-assembled from a biodegradable cationic copolymer P(MDS-co-CES) to achieve synergistic cytotoxic effects in cancer cells. Effects of nanocomplexes on both wild type and TRAIL-resistant SW480 colorectal carcinoma cells were investigated. Cytotoxicity of the nanocomplexes to non-cancerous cells was significantly lower than cancerous cells. Anti-proliferative effects of nanocomplexes were retained in remaining cancer cells in long-term cultures after treatment with the nanocomplexes. In summary, this Dox and TRAIL co-delivery system can be a promising candidate for cancer treatment.